Early Short-Term Use of Different Doses of Corticosteroid in Hospitalized Pediatric Patients with Coronavirus Disease 2019 Pneumonia - Özen, Seval; Gülhan, Belgin; Yüksek, Saliha Kanik; Güney, Ahmet Yasin; Erat, Tuğba; Yahşi, Aysun; Güneş, Ömer; Güder, Latife; Mustafaoğlu, Özlem; Bayraktar, Pınar; Üçkardeş, Fatih; Emeksiz, Serhat; Bayhan, Gülsüm İclal; Parlakay, Aslınur Özkaya (Journal of Pediatric Infectious Diseases, 2022)
Objective Encouraged by reports of favorable outcomes following the use of corticosteroids in patients with moderate-to-severe coronavirus 2019 (COVID-19) pneumonia, we aimed to present our experience with early short-term corticosteroid use at our center in pediatric patients with COVID-19 pneumonia.Methods One hundred and twenty-nine pediatric patients were included in the study. Patients were divided into four groups according to the type and dose of corticosteroids given: Group 1 (those receiving dexamethasone 0.15 mg/kg/d); Group 2 (those receiving methylprednisolone 1 mg/kg/d); Group 3 (those receiving methylprednisolone 2 mg/kg/d); and Group 4 (those receiving pulse methylprednisolone 10–30 mg/kg/d).Results Of 129 patients, 19 (14.7%) patients were assigned to Group 1, 30 (23.3%) patients to Group 2, 30 (23.3%) patients to Group 3, and 50 (38.8%) patients to Group 4. Thirty-two (24.8%) patients were followed in the pediatric intensive care unit (PICU), of whom 13 (10%) required mechanical ventilation, and 7 (%5.4) died. In Group 4, the hospitalization length was significantly longer than in other groups (p < 0.001, p < 0.001). No significant difference was found among the groups in terms of mortality (p = 0.15). The most common comorbidity was obesity (33%). A significant association was found between the presence of comorbidity and mortality (p < 0.001). All patients who died had an underlying disease. Cerebral palsy was the most common underlying disease among the patients who died. Worsening of lymphopenia was significant in patients with severe COVID-19 pneumonia at the time of transfer to the PICU (p = 0.011).Conclusion Although children usually have a milder course of COVID-19 than adults, underlying diseases and obesity increase the severity of disease manifestations also in children. Further studies are needed to define the exact role of corticosteroids in COVID-19 patients.
Keywords: Methylprednisolone; dexamethasone; COVID-19; pneumonia; lymphopenia; pediatric